Terahertz Metasurfaces: Toward Multifunctional and Programmable Wave Manipulation - Tian, Han Wei; Shen, Hai Yang; Zhang, Xin Ge; Li, Xin; Jiang, Wei Xiang; Cui, Tie Jun (Frontiers in Physics, 2020)
Metasurface, composed of prearranged artificial unit cells possessing different electromagnetic (EM) responses, provides unprecedented abilities to realize versatile wave manipulations. Especially in the terahertz spectrum, metasurface attracts broad attention by opening up further possibilities for wave regulating. Terahertz applications in various fields, for instance, spatial light modulation (SLM), radar, imaging, time-domain spectroscopy (TDS) and high-speed communication, have got facilitated and improved. In this article, we first give a simply review on recent advances of terahertz metasurfaces, including discussion of passive metasurfaces with fixed structures and active metasurfaces integrated with tunable components. Then, we briefly retrospect the development of coding metasurfaces and programmable metasurfaces represented by digitized bits. We mainly focus on some powerful functions, functional multiplexing, and real-time controlled applications in terahertz frequencies. Finally, we give an abbreviated prospection of developing terahertz multifunctional metasurfaces and programmable metasurfaces.